Radial symmetry results for fractional Laplacian systems. (November 2016) - Liu, Baiyu; Ma, Li
Abstract: In this paper, we generalize the direct method of moving planes for the fractional Laplacian to the system case. Considering a coupled nonlinear system with fractional Laplacian, we first establish a decay at infinity principle and a narrow region principle. Using these principles, we then obtain two radial symmetry results for the decaying solutions of the fractional Laplacian systems. Finally, we apply our method to fractional Schrödinger systems and fractional Hénon systems.